Neurociência e o ensino da matemática: uma revisão bibliográfica - SILVA JÚNIOR, Elias Araújo da (2022)
This present works seeks to deal with neuroscience applied to the field of mathematics, because education must be prioritized and have in itself the application of pedagogical and neuropsychopedagogical methods, in order to benefit the student in their learning process. The objective of this work is to seek to analyze the main theories of teaching and learning, based on neuroscience, in order to contribute to an increasingly deeper learning in mathematical language by students. To achieve the general objective in question, the following specific objectives are: Conceptualize neuroscience and cognitive neuroscience; investigate the connection between neuroscience and an individual's learning process, mainly in the area of mathematics; analyze and comment about the main theories of learning and among these, highlight which has a greater link with teaching and learning, based on neuroscience. The choice of this theme is justified by the importance of carrying out daily activities such as checking change and the bank account, helping children with their schoolwork, as well as making sense of statistical data and understanding news about health and economics, because the Math is part of our daily lives. In general, people make their decisions based on numerical information, so knowing how to interpret them allows the individual to make better choices throughout his life. The research methodology will be bibliographic research based on document analysis and literary review. Throughout the work, it was possible to present evolutionary aspects of the human brain, neuroscience and its application in cognition and the teaching of mathematics in Brazil.